Pengaruh Profitabilitas dan Kebijakan Dividen terhadap Nilai Perusahaan dengan Corporate Social Responsibility (CSR) sebagai Variabel Moderasi - Ristia Ristia; Addiarrahman Addiarrahman (Lembaga Yasin AlSys, 2026)
Firm value is a central issue in finance; however, studies that specifically position Corporate Social Responsibility (CSR) as a moderating variable in sharia-based companies remain limited. This study aimed to analyze the effect of profitability and dividend policy on firm value with CSR as a moderating variable in consumer goods industry sector companies listed on the Indeks Saham Syariah Indonesia (ISSI) for the 2019–2023 period. The research employed a quantitative approach with an explanatory research design, and the sample was determined using a purposive sampling technique. Secondary data were obtained from companies’ financial statements and sustainability reports, and were analyzed using multiple linear regression and moderation testing with the aid of EViews software. The results showed that profitability and dividend policy did not have a significant effect on firm value. However, CSR was found to positively and significantly moderate the effect of dividend policy on firm value, while it did not moderate the effect of profitability. These findings underscore the important role of CSR in strengthening the influence of dividend policy on enhancing firm value and contribute to the development of signaling and legitimacy theories, while also providing practical implications for management and investors in sustainability-based financial decision-making.